Pendugaan Bobot Hidup Sapi Peranakan Ongole (PO) dan Sapi Pesisir Menggunakan Pencitraan Digital - Riffiandi, N.; Priyanto, R.; Nuraini, N. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2015)
This research aimed to estimate cattlelive weight by digital imageanalysis using two variables, namely side body surface area (LPTS) and back body surface area (LPTB). Thestudyused 40 heads of PO cattle and 45 heads Pesisir cattle. The body surface of cattle was visualized by digital camera and the image was analyse by autocad software. The combination of LPTS and LPTB was correlated to live weight of cattle with coefficient determinatoin (R2) of 70.57 % and 40.96 % for PO and Pesisir cattle respectively. The established regretion equation gave standard error of 51.63 kg for PO cattle and 25.54 kg for Pesisir cattle. Therefore, the estimation of cattle live weight based on LPTS and LPTB was not suggested as their hight prediction error.